Russian Federation : Report on Observance of Standards and Codes-Data Module. (IMF Staff Country Reports; Country Report, 2011)
The report covers national accounts, prices (consumer and producer prices), government finance, monetary, financial and international accounts (balance-of-payments and international investment position) statistics. Assessment of macroeconomic datasets was conducted using data quality assessment framework (DQAF). With the assistance of the Central Bank of Russian Federation (CBR), users' survey was conducted. Users are satisfied with the methodological soundness, coverage, timeliness, and accessibility of official statistics, especially monetary and financial and balance of payments statistics. Based on the review, the mission has developed a set of recommendations.